Physical and Strength Properties of Cements Manufactured in Bangladesh: A Case Study - Ahmed, Khondaker S; Asef, Mohammad F; Ahmed, Mahfuj (MIST International Journal of Science and Technology, 2022)
This study investigates the physical qualities and strength properties of representative cements manufactured by different brands in Bangladesh. The physical and strength properties such as normal consistency, initial and final setting time, density, specific gravity, fineness, and compressive strength of cement mortars as well as concrete cylinders were investigated experimentally. Using CEM II/B-M type cement, a total of 300 test specimens are prepared to determine those parameters. In this case study, specimens were prepared from ten different representative cement industries of Bangladesh and tested as per ASTM specifications. The experimental result shows that the physical and strength parameters of nearly all the representative cement samples are within the ASTM recommended ranges that ultimately proofs the quality of Bangladeshi Cement. The relationship between mortar and concrete strengths from the same batch of cement has also been investigated. Besides, a regression analysis has been conducted to find relationships between the concrete strength and their age of curing. The influence of initial and final setting times on concrete strength is also investigated. This study also provides the relationships between compressive strengths, between mortar and concrete cylinders at different ages. These age dependencies of concrete strength will help to predict the actual concrete strength at the early age of curing which may ensure faster construction work. MIJST, Vol. 10(1), June 2022: 49-59